2006
DOI: 10.1111/j.1541-1338.2006.00247.x
|View full text |Cite
|
Sign up to set email alerts
|

Elementary Grade Retention in Texas and Reading Achievement Among Racial Groups: 1994–2002

Abstract: Students who failed the Texas mandatory third grade reading test were followed through their sophomore year in high school. Comparisons of reading scores between third grade students who repeated the grade and their socially promoted classmates revealed that the positive effect of retention persisted over time. Retention in third grade benefited low‐performing readers regardless of race. Supplemental analyses found that the results are not likely attributable to selection biases, differential attrition of stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…For example, if the retention decision was made in 1st grade, the performance of promoted students the following year, when they were in 2nd grade for the first time would be compared to the performance of retained students two years later, when they were in 2nd grade for the first time. Educators have suggested that same grade comparisons are more reasonable than same age comparisons in studies of the effect of retention on achievement, because same age comparisons test retained students over content that they have not yet encountered (Wu, West, & Hughes, 2008b; Lorence & Dworkin, 2006). …”
Section: Results Of Prior Studies With Current Longitudinal Samplementioning
confidence: 99%
“…For example, if the retention decision was made in 1st grade, the performance of promoted students the following year, when they were in 2nd grade for the first time would be compared to the performance of retained students two years later, when they were in 2nd grade for the first time. Educators have suggested that same grade comparisons are more reasonable than same age comparisons in studies of the effect of retention on achievement, because same age comparisons test retained students over content that they have not yet encountered (Wu, West, & Hughes, 2008b; Lorence & Dworkin, 2006). …”
Section: Results Of Prior Studies With Current Longitudinal Samplementioning
confidence: 99%
“…In many countries, the practice of grade retention is widespread (Switzerland: Bonvin, Bless, & Schuepbach, 2008;Germany: Ehmke, Drechsel, & Carstensen, 2010;US: Jimerson, 2001;Lorence & Dworkin, 2006;Canada: Pagani, Tremblay, Vitaro, Boulerice, & McDuff, 2001;Belgium: Juchtmans et al, 2011;Van Petegem & Schuermans, 2005). Proponents believe that giving students ''the gift of time'' will put them back on track for normal educational growth.…”
Section: Introductionmentioning
confidence: 99%
“…Xia and Kirby (2009) found that the vast majority of studies that demonstrated immediate gains from retention also showed that those effects began to dissipate two to three years after the retention, and completely disappeared after several years with retained students falling behind again. Lorence and Dworkin's (2006) and Lorence, Dworkin, Toenjes, and Hill's (2002) studies in Texas and Alexander, Entwisle, and Dauber's (1994) longitudinal study in Baltimore found much longer-lasting positive effects of retention, but they too decreased over time. Xia and Kirby (2009) did note that in some of these studies where students showed longer-lasting gains (e.g., Lorence & Dworkin, 2006), an intervention was also provided; however, researchers were unable to determine if the improvement was linked to retention or intervention.…”
Section: Retention Meta-analyses and Reviewsmentioning
confidence: 94%